Separator for lithium secondary battery and lithium secondary battery equipped with same

JP7608008B2Active Publication Date: 2025-01-06LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022564645
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-19
Filing Date
2021-10-18
Publication Date
2025-01-06
Estimated Expiration
2041-10-18

AI Technical Summary

Benefits of technology

【0023】 本発明の一実施形態によるリチウム二次電池用セパレーターは、モース硬度3.5~8.5の無機物粒子、及び70℃での貯蔵弾性率(storage modulus)500Mpa以上の第1バインダー高分子を含むことにより、多孔性コーティング層がセパレーターへの外部応力を吸収することができながらも多孔性高分子基材の損傷を防止することができるうえ、優れた耐圧縮性を有することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608008000005
    Figure 0007608008000005
  • Figure 0007608008000006
    Figure 0007608008000006
  • Figure 0007608008000007
    Figure 0007608008000007
Patent Text Reader

Abstract

The present invention relates to a separator for a lithium secondary battery, which includes a porous polymer substrate and a porous coating layer located on at least one surface of the porous polymer substrate and including inorganic particles having a Mohs hardness of 3.5 to 8.5 and a binder polymer, wherein the binder polymer includes a first binder polymer having a storage modulus of 500 MPa or more at 70°C, and a lithium secondary battery including the separator, wherein the separator has excellent compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention claims priority to Korean Patent Application No. 10-2020-0135019, filed on October 19, 2020.

[0002] The present invention relates to a separator for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]

[0003] Recently, interest in energy storage technology has been increasing. As the fields of application expand to include mobile phones, camcorders, notebook computers, and even electric vehicles, there is a growing demand for higher energy density batteries used as power sources for such electronic devices. Lithium secondary batteries are the batteries that can best meet such demands, and research into them is currently being actively conducted.

[0004] Such a lithium secondary battery generally includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a non-aqueous electrolyte including a lithium salt and an organic solvent, and a separator interposed between the positive electrode and the negative electrode to electrically insulate them.

[0005] However, when a separator and an electrode are laminated to manufacture a lithium secondary battery, the separator may be locally compressed due to heat and pressure. The separator may also be locally compressed due to volume expansion that occurs as charge / discharge cycles proceed. Lithium dendrites may be formed in the locally compressed area, which may cause an internal short circuit.

[0006] In particular, in recent years, in order to increase the energy density of lithium secondary batteries, metal oxides have increasingly been used as negative electrodes instead of graphite. However, such metal oxides have a high hardness, which may further increase problems caused by separator compression.

[0007] In addition, in the case of a separator in which a porous coating layer containing inorganic particles and a binder polymer is formed on at least one surface of a polyolefin-based porous substrate that is commonly used as a separator, the porous polymer substrate may be locally compressed by the inorganic particles. If the porous coating layer itself is compressed by heat and pressure in this manner, problems such as an increase in resistance due to clogging of the pores of the porous coating layer may occur.

[0008] Therefore, the actual situation is that there is a very high demand for separators that are capable of absorbing external stresses applied to the separator and therefore have excellent compression resistance. Summary of the Invention [Problem to be solved by the invention]

[0009] Therefore, an object of the present invention is to provide a separator for a lithium secondary battery having excellent compression resistance, and a lithium secondary battery including the separator. [Means for solving the problem]

[0010] In order to solve the above problems, according to one aspect of the present invention, there is provided a separator for a lithium secondary battery according to the following embodiment.

[0011] The first embodiment is A porous polymer substrate; The porous coating layer is located on at least one surface of the porous polymer substrate and includes inorganic particles having a Mohs hardness of 3.5 to 8.5 and a binder polymer; The present invention relates to a separator for a lithium secondary battery, wherein the binder polymer includes a first binder polymer having a storage modulus at 70° C. of 500 MPa or more.

[0012] The second embodiment is the same as the first embodiment, The inorganic particles can include TiO2, SiO2, or two or more thereof.

[0013] The third embodiment is the same as the first or second embodiment, The first binder polymer may include polyvinylidene fluoride-co-hexafluoropropylene containing 1% by weight to 3% by weight of hexafluoropropylene (HFP) monomer, poly(acrylic acid)-co-poly(vinyl alcohol) copolymer, or two or more of these.

[0014] The fourth embodiment is any one of the first to third embodiments, The binder polymer may further include a second binder polymer having a storage modulus at 70° C. of 50 MPa or less.

[0015] The fifth embodiment is the same as the fourth embodiment, The weight ratio of the first binder polymer to the second binder polymer may be 0.8:1 to 1.2:1.

[0016] The sixth embodiment is the same as the fourth or fifth embodiment, The second binder polymer is selected from the group consisting of polyvinylidene fluoride-co-trichloroethylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, or two or more of these.

[0017] The seventh embodiment is any one of the first to sixth embodiments, The thickness reduction rate of the separator during lamination of the electrode and the separator may be 7% or less.

[0018] The eighth embodiment is any one of the first to seventh embodiments, The porous coating layer may further include a dispersant.

[0019] The ninth embodiment is the same as the eighth embodiment, The dispersing agent may include a cyano resin containing a CN (cyano group), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polymethacrylic acid (PMAA), or two or more of these.

[0020] The tenth embodiment is any one of the first to ninth embodiments, The inorganic particles may be included in an amount of 20 wt % to 99.9 wt % based on 100 wt % of the porous coating layer.

[0021] In order to solve the above problems, according to one aspect of the present invention, there is provided a lithium secondary battery of the following embodiment.

[0022] The eleventh embodiment is A battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, The present invention relates to a lithium secondary battery, wherein the separator is the lithium secondary battery separator according to any one of the first to tenth embodiments. Effect of the Invention

[0023] The separator for a lithium secondary battery according to one embodiment of the present invention includes inorganic particles having a Mohs hardness of 3.5 to 8.5 and a first binder polymer having a storage modulus of 500 MPa or more at 70°C, so that the porous coating layer can absorb external stress on the separator while preventing damage to the porous polymer substrate, and has excellent compression resistance.

[0024] In addition, the separator for a lithium secondary battery according to an embodiment of the present invention can prevent the porous coating layer from being compressed due to an external stress, thereby improving air permeability.

[0025] Specifically, in the separator for a lithium secondary battery according to an embodiment of the present invention, the thickness reduction rate of the separator, more specifically, the thickness reduction rate of the porous polymer substrate included in the separator, is 7% or less under lamination conditions of the electrode and the separator.

[0026] The separator for a lithium secondary battery according to an embodiment of the present invention can improve cycle life by minimizing compression of the separator due to external stress, and can alleviate the problem of internal short circuit.

[0027] The separator for a lithium secondary battery according to an embodiment of the present invention further includes a second binder polymer having a storage modulus of 50 MPa or less at 70° C. in addition to a first binder polymer having a storage modulus of 500 MPa or more at 70° C., and thus has excellent compression resistance, improved air permeability, and excellent electrode adhesion. [Brief description of the drawings]

[0028] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the above-mentioned content of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited only to the matters depicted in such drawings.

[0029] [Figure 1] 1 shows storage modulus values ​​according to temperature changes of binder polymers used in Example 1-1, Comparative Example 1-1, and Comparative Example 1-2 of the present invention. [Diagram 2]2 shows a cross-sectional SEM image of a separator in a lithium secondary battery produced in Example 2-2 of the present invention. [Diagram 3] 1 shows a cross-sectional SEM image of a separator in a lithium secondary battery produced in Comparative Example 2-2 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. Prior to this, the terms or words used in the present specification and claims should not be interpreted limitedly to their ordinary and dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.

[0031] Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can replace them at the time of filing this application.

[0032] According to one embodiment of the present invention, there is provided a separator for a lithium secondary battery, comprising: a porous polymer substrate; and a porous coating layer disposed on at least one surface of the porous polymer substrate, the porous coating layer including inorganic particles having a Mohs hardness of 3.5 to 8.5 and a binder polymer, the binder polymer including a first binder polymer having a storage modulus of 500 MPa or more at 70°C.

[0033] In one embodiment of the present invention, the porous polymer substrate can be used without any particular limitation as long as it can be used as a material for a separator for a lithium secondary battery. Such a porous polymer substrate is a thin film containing a polymer material, and non-limiting examples of the polymer material include at least one of polymer resins such as polyolefin resin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene. In addition, the porous polymer substrate can be a nonwoven fabric or a porous polymer film formed of the polymer material, or a laminate of two or more of these. Specifically, the porous polymer substrate can be any one of the following a) to e).

[0034] a) a porous film formed by melting and extruding a polymer resin; b) a multilayer film having two or more layers of the porous film of a) laminated thereon; c) a nonwoven web produced by accumulating filaments obtained by melting / spinning a polymer resin; d) a multilayer film having two or more layers of the nonwoven fabric web of c) laminated thereon; e) A multi-layered porous membrane comprising two or more of a) to d).

[0035] In one embodiment of the present invention, the thickness of the porous polymer substrate 10 may be 5 μm to 50 μm. The thickness range of the porous polymer substrate is not particularly limited to the above range, but when the thickness is within the above range, the problem that the separator may be easily damaged during use of the battery can be prevented and the energy density can be ensured. Meanwhile, the pore size and porosity present in the porous polymer substrate are also not particularly limited, but may be 0.01 μm to 50 μm and 10% to 95%, respectively.

[0036] In the present invention, the porosity and pore size of the porous polymer substrate 10 can be measured by a BET 6-point method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porometer, or a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.) by a nitrogen gas adsorption flow method. In this case, it may be advantageous to use a capillary flow porometer.

[0037] In the separator for a lithium secondary battery according to an embodiment of the present invention, the porous coating layer is located on at least one surface of the porous polymer substrate. For example, the porous coating layer may be located on one or both surfaces of the porous polymer substrate.

[0038] In the separator for a lithium secondary battery according to one embodiment of the present invention, the porous coating layer includes inorganic particles having a Mohs hardness of 3.5 to 8.5, and a binder polymer (not shown) that bonds the inorganic particles (not shown) to each other (i.e., the binder polymer connects and fixes the inorganic particles) so that the inorganic particles (not shown) can be maintained in a bound state. The porous coating layer can improve the safety of the separator by preventing the porous polymer substrate from exhibiting extreme thermal shrinkage behavior at high temperatures due to the inorganic particles.

[0039] In the present invention, the binder polymer includes a first binder polymer having a storage modulus of 500 MPa or more at 70° C. In the present invention, the term “storage modulus” refers to the magnitude of elastic energy stored in a vibrating sample.

[0040] The separator for a lithium secondary battery according to one embodiment of the present invention includes a first binder polymer having a storage modulus of 500 MPa or more at 70° C., and thus a porous coating layer including the first binder polymer can absorb external stress on the separator to prevent compression of the separator and improve the air permeability of the separator.

[0041] Meanwhile, when a lithium secondary battery having a separator and an electrode laminated thereon is manufactured by laminating the separator and the electrode under conditions of generally 60°C to 70°C and a pressure of 2.4kgf / mm to 3.2kgf / mm, the separator may be locally compressed due to the heat and pressure applied during the lamination process.

[0042] The separator for a lithium secondary battery according to an embodiment of the present invention includes a first binder polymer having a high storage modulus under such lamination temperature conditions, and thus may have excellent compression resistance against heat and pressure applied to the separator during the lamination process.

[0043] In the present invention, the storage modulus of the binder polymer at 70° C. can be measured by dynamic mechanical analysis (DMA).

[0044] In one embodiment of the present invention, the thickness reduction rate of the separator, more specifically the porous polymer substrate, may be 7% or less in the temperature range in which the separator and the electrodes are laminated. When the thickness reduction rate of the porous polymer substrate in the temperature range in which the separator and the electrodes are laminated satisfies the above range, it is possible to prevent an increase in the rate of internal short circuit defects due to local deformation of the porous polymer substrate. In the separator for a lithium secondary battery according to one embodiment of the present invention, the thickness reduction rate of the porous polymer substrate is 7% or less in the temperature range in which the separator and the electrodes are laminated, thereby minimizing damage to the separator and improving the performance of the lithium secondary battery that is affected by the thickness of the separator.

[0045] The thickness reduction rate of the separator under lamination conditions of the electrode and the separator can be measured by compressing the separator at 70° C. and a pressure of 7.4 MPa using a hot press, and then measuring the thickness of the separator, for example, a porous polymer substrate.

[0046] At this time, the thickness reduction rate can be measured by the following formula. Thickness reduction rate of porous polymer substrate at 70°C and 7.4Mpa = (thickness of porous polymer substrate at initial manufacture - thickness of porous polymer substrate at 70°C and 7.4Mpa) / thickness of porous polymer substrate at initial manufacture

[0047] If the storage modulus of the first binder polymer at 70° C. is less than 500 MPa, the porous coating layer cannot sufficiently absorb the external stress on the separator. As a result, the external stress is directly transferred to the porous polymer substrate, causing deformation of the separator, which may increase the rate of internal short circuit defects. In this case, the thickness reduction rate of the porous polymer substrate may exceed 7%.

[0048] In addition, the separator for a lithium secondary battery according to an embodiment of the present invention may have an air permeability of less than 2000s / 100cc in a temperature range in which the separator and the electrodes are laminated. When the air permeability of the separator is less than 2000s / 100cc, the battery output and cycle life characteristics may be further improved.

[0049] The air permeability of the separator is such that 100cc of air passes through 1 in of the separator under a pressure of 12.2 inH2O. 2 The time it takes for a gas to pass through a cross section of the material, i.e., the airflow time, can be measured.

[0050] In an embodiment of the present invention, the first binder polymer may include polyvinylidene fluoride-co-hexafluoropropylene containing 1 wt % to 3 wt % hexafluoropropylene (HFP) monomer, poly(acrylic acid)-co-poly(vinylalcohol), or two or more thereof.

[0051] In an embodiment of the present invention, the binder polymer may further include a second binder polymer having a storage modulus of 50 MPa or less at 70° C. in addition to the first binder polymer. The second binder polymer has a storage modulus of 50 MPa or less at 70° C. and can contribute to improving the adhesive strength of the separator to the electrode.

[0052] In one embodiment of the present invention, when the binder polymer further includes a second binder polymer in addition to the first binder polymer, the distribution of the first binder polymer and the second binder polymer in the porous coating layer is not limited to the following, but the first binder polymer may be located more abundantly than the second binder polymer at the surface of the porous coating layer (the content of the first binder polymer is higher than the weight ratio of the first binder polymer and the second binder polymer when initially added). In contrast, the second binder polymer may be present throughout the thickness direction of the porous coating layer and / or may be located more abundantly than the first binder polymer at the interface between the porous coating layer and the porous polymer substrate (the content of the second binder polymer is higher than the weight ratio of the first binder polymer and the second binder polymer when initially added).

[0053] In this case, the first binder polymer can contribute to the adhesive strength between the surface of the porous coating layer and the electrode, and the second binder polymer can contribute to improving the adhesive strength between the porous polymer substrate and the porous coating layer, so that a separator having excellent adhesive strength between the porous coating layer and the porous polymer substrate and excellent adhesive strength to the electrode can be provided. As a result, the separator can have excellent compression resistance and improved air permeability, and also has excellent adhesive strength between the separator and the electrode.

[0054] In an embodiment of the present invention, the weight ratio of the first binder polymer to the second binder polymer may be 0.8:1 to 1.2:1, 0.9:1 to 1.1:1, or about 1: 1. When the weight ratio of the first binder polymer to the second binder polymer satisfies the above range, the separator may have excellent compression resistance, improved air permeability, and excellent adhesive strength between the separator and the electrodes.

[0055] In one embodiment of the present invention, the second binder polymer is selected from the group consisting of polyvinylidene fluoride-co-trichloroethylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, or two or more of these.

[0056] The separator for a lithium secondary battery according to one embodiment of the present invention includes inorganic particles having a Mohs hardness of 3.5 to 8.5 together with a first binder polymer having a storage modulus of 500 MPa or more at 70° C. The separator for a lithium secondary battery according to one embodiment of the present invention includes inorganic particles having a Mohs hardness of 3.5 to 8.5 together with a first binder polymer having a storage modulus of 500 MPa or more at 70° C. The inorganic particles and the first binder polymer containing the inorganic particles can absorb external stress to prevent compression of the porous coating layer due to external stress, and the porous coating layer can prevent damage to the porous polymer substrate.

[0057] In the present invention, "Mohs hardness" is a value evaluated by comparing the hardness with 10 types of minerals (Mohs hardness 1: talc, Mohs hardness 2: gypsum, Mohs hardness 3: calcite, Mohs hardness 4: fluorite, Mohs hardness 5: apatite, Mohs hardness 6: orthoclase, Mohs hardness 7: quartz, Mohs hardness 8: topaz, Mohs hardness 9: corundum, Mohs hardness 10: diamond) that are used as standard substances. The standard substances and the sample are rubbed against each other, and the side that generates scratches is determined to have a lower hardness.

[0058] When the Mohs hardness of the inorganic particles is less than 3.5, damage to the porous polymer substrate can be prevented by the Mohs hardness of the inorganic particles, but since the inorganic particles cannot adequately absorb external stress, problems may occur due to compression of the separator, particularly the porous polymer substrate, even if the separator contains a first binder polymer described below. In addition, since the inorganic particles cannot adequately absorb external stress, the porous coating layer itself may be compressed by the external stress, causing the pores of the porous coating layer to become clogged. This may reduce the air permeability of the separator.

[0059] When the Mohs hardness of the inorganic particles exceeds 8.5, the porous coating layer including the inorganic particles and the first binder polymer described below can absorb external stress, but since the Mohs hardness of the inorganic particles is so high, the inorganic particles may instead apply stress to the porous polymer substrate, damaging the porous polymer substrate, which may cause problems due to compression of the porous polymer substrate.

[0060] In one embodiment of the present invention, the inorganic particles may have a Mohs hardness of 4.0 to 8.0, or 5.0 to 7.5, or 7.0 to 7.5.

[0061] In one embodiment of the present invention, the inorganic particles having a Mohs hardness of 3.5 to 8.5 can include, for example, TiO2, SiO2, or two or more of these.

[0062] In one embodiment of the present invention, the size of the inorganic particles is not limited, but may have an average particle size in the range of about 0.01 to about 10 μm, or 0.05 to 1.0 μm. When the inorganic particle size satisfies this range, the dispersibility is maintained, the physical properties of the separator are easily controlled, and the mechanical properties can be improved. In addition, the probability of an internal short circuit occurring during charging and discharging of the battery due to a too large pore size can be reduced.

[0063] In this case, the average particle size of the inorganic particles means the D50 particle size, and "D50 particle size" means the particle size at 50% of the cumulative particle number distribution by particle size. The particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size is measured when the particles pass through a laser beam to calculate the particle size distribution. The D50 particle size can be measured by calculating the particle size at the 50% point of the cumulative particle number distribution by particle size in the measuring device.

[0064] In one embodiment of the present invention, the inorganic particles may be included in an amount of 20 wt % to 99.9 wt % based on 100 wt % of the porous coating layer.

[0065] In one embodiment of the present invention, the porous coating layer may further include other additives commonly used in the art in addition to the inorganic particles, the first and second binder polymers.

[0066] In one embodiment of the present invention, the porous coating layer may further include a dispersant. The dispersant may include, for example, a cyano resin containing a cyano group (CN), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polymethacrylic acid (PMAA), or two or more of these. When the porous coating layer further includes a dispersant, the dispersibility of inorganic particles may be further improved.

[0067] In one embodiment of the present invention, the dispersant may be included in an amount of 0.5 wt% to 2.0 wt%, 1.0 wt% to 1.7 wt%, or about 1.5 wt% based on 100 wt% of the porous coating layer. When the content of the dispersant satisfies the above range, the inorganic particles in the porous coating layer are prevented from agglomerating with each other, and the inorganic particles are easily dispersed uniformly.

[0068] In one embodiment of the present invention, the porous coating layer may have a structure in which the inorganic particles are filled and in contact with each other and bound to each other by the binder polymer, thereby forming interstitial volumes between the inorganic particles, and the interstitial volumes between the inorganic particles may become void spaces to form pores.

[0069] In one embodiment of the present invention, the pore size of the porous coating layer may be in the range of 0.001 to 10 μm or 0.001 to 1 μm. Furthermore, the porosity of the porous coating layer may be in the range of 5 to 95%, 10 to 95%, 20 to 90%, or 30 to 80%. The porosity corresponds to a subtraction value obtained by subtracting the volume calculated from the weight and density of each component of the porous coating layer from the volume calculated in the thickness, width, and length of the porous coating layer.

[0070] In the present invention, the porosity and pore size of the porous coating layer can be measured by a BET 6-point method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porometer, or a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.) by a nitrogen gas adsorption flow method. In this case, it may be advantageous to use a capillary flow porometer.

[0071] In one embodiment of the present invention, the porous coating layer may have a thickness in the range of 1 μm to 50 μm, or 2 μm to 30 μm, or 2 μm to 20 μm.

[0072] The separator for a lithium secondary battery according to one embodiment of the present invention can be produced by the following production method, but is not limited thereto.

[0073] A method for producing a separator for a lithium secondary battery according to one embodiment of the present invention includes the steps of: Providing a porous polymeric substrate; and coating at least one surface of the porous polymer substrate with a slurry including inorganic particles, a binder polymer, and a solvent for the binder polymer, and then drying the slurry to form a porous coating layer. The binder polymer is characterized by including a first binder polymer having a storage modulus at 70° C. of 500 MPa or more.

[0074] Hereinafter, a method for producing a separator for a lithium secondary battery according to one embodiment of the present invention will be described with a focus on the main parts.

[0075] First, a porous polymer substrate is prepared. The porous polymer substrate can be used as described above, and the porous polymer substrate can be manufactured by forming pores through a conventional method known in the art, such as a wet method using a solvent, diluent or pore-forming agent, or a dry method using a stretching method, in order to ensure excellent breathability and porosity from the above-mentioned material.

[0076] Thereafter, a slurry containing inorganic particles, a binder polymer, and a solvent for the binder polymer is coated on at least one surface of the porous polymer substrate, and then dried to form a porous coating layer.

[0077] For the inorganic particles, please refer to the above contents.

[0078] The binder polymer includes a first binder polymer having a storage modulus at 70° C. of 500 MPa or more.

[0079] In an embodiment of the present invention, the first binder polymer may include polyvinylidene fluoride-co-hexafluoropropylene containing 1 wt % to 3 wt % hexafluoropropylene (HFP) monomer, poly(acrylic acid)-co-poly(vinyl alcohol) copolymer, or two or more thereof.

[0080] In an embodiment of the present invention, the binder polymer may further include a second binder polymer having a storage modulus of 50 MPa or less at 70° C. in addition to the first binder polymer. The second binder polymer has a storage modulus of 50 MPa or less at 70° C. and can contribute to improving the adhesive strength of the separator to the electrode.

[0081] The content ratio of the first binder polymer to the second binder polymer is as described above.

[0082] In one embodiment of the present invention, the second binder polymer is selected from the group consisting of polyvinylidene fluoride-co-trichloroethylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, or two or more of these.

[0083] The solvent for the binder polymer can function as a solvent that dissolves the binder polymer or as a dispersion medium that disperses the binder polymer without dissolving it, depending on the type of binder polymer. Specifically, the solvent for the binder polymer can function as a solvent that dissolves the first binder polymer or as a dispersion medium that disperses the first binder polymer without dissolving it.

[0084] In an embodiment of the present invention, when the binder polymer further includes a second binder polymer in addition to the first binder polymer, the solvent for the binder polymer may function as a solvent that dissolves both the first and second binder polymers, or may function as a dispersion medium that disperses the first and second binder polymers without dissolving them.

[0085] In one embodiment of the present invention, the solvent for the binder polymer may include, but is not limited to, acetone, dimethyl acetamide (DMAc), dimethylformamide (DMF), tetrahydrofuran, methylene chloride (MC), chloroform, N-methyl-2-pyrrolidone (NMP), cyclohexane, or two or more of these.

[0086] In one embodiment of the present invention, the method of coating the slurry on at least one surface of the porous polymer substrate to form a porous coating layer is not limited, and may be a dip coating method, a die coating method, a roll coating method, a comma coating method, a doctor blade coating method, a reverse roll coating method, a direct roll coating method, or the like.

[0087] In one embodiment of the present invention, a phase separation process may be performed to form a better pore structure in the porous coating layer. The phase separation process refers to a process of forming a pore structure in the porous coating layer by a phase separation phenomenon known in the art. For example, the phase separation process may be performed by a wet phase separation method or a immersion phase separation method.

[0088] Next, the humidification phase separation, which is one of the phase separations, will be described.

[0089] The humid phase separation means that the porous polymer substrate coated with the slurry is exposed to a non-solvent atmosphere for the first binder polymer, causing phase separation. In this case, the non-solvent can be introduced in a gaseous state. The humid phase separation can be performed under conditions of 23°C to 32°C, or 25°C to 30°C, and a relative humidity of 45% to 60%, or 50% to 55%. When the humid phase separation is performed in the above-mentioned temperature range, the porous coating layer can be dried in a short time while a sufficient time required for phase separation of the first binder polymer can be secured. When the humid phase separation is performed in the above-mentioned pressure range, the problem of condensation of moisture in a drying oven can be prevented while a sufficient amount of non-solvent is included that allows humid phase separation to occur.

[0090] In one embodiment of the present invention, when the second binder polymer is further included in addition to the first binder polymer, the humid phase separation means that the porous polymer substrate coated with the slurry is exposed to a non-solvent atmosphere for the first and second binder polymers, and thus phase separation occurs. In this case, the non-solvent can be introduced in a gaseous state. The humid phase separation can be performed under conditions of 23°C to 32°C, or 25°C to 30°C, and a relative humidity of 45% to 60%, or 50% to 55%. When the humid phase separation is performed in the above-mentioned temperature range, the porous coating layer can be dried in a short time while a sufficient time required for phase separation of the first and second binder polymers can be secured. When the humid phase separation is performed in the above-mentioned pressure range, the problem of moisture condensation in a drying oven can be prevented while a sufficient amount of non-solvent is included that allows humid phase separation to occur.

[0091] Next, the immersion phase separation, which is one of the phase separation methods, will be described.

[0092] The porous polymer substrate coated with the slurry is immersed in a coagulation liquid containing a non-solvent for the first binder polymer for a predetermined period of time. During this process, the first binder polymer solidifies and the coated slurry becomes porous. The coagulation liquid is then removed by washing with water, and the substrate is dried. In the immersion phase separation, the non-solvent may be contained in an amount of 60% by weight or more relative to 100% by weight of the coagulation liquid, from the viewpoint of forming a good porous structure and improving productivity.

[0093] In one embodiment of the present invention, when the second binder polymer is further included in addition to the first binder polymer, the porous polymer substrate coated with the slurry is immersed in a coagulation liquid containing a non-solvent for the first and second binder polymers for a predetermined time. During this process, the first and second binder polymers are solidified and the coated slurry becomes porous. Thereafter, the coagulation liquid is removed by washing with water, and the substrate is dried. In the immersion phase separation, the non-solvent may be included in an amount of 60% by weight or more relative to 100% by weight of the coagulation liquid in order to form a good porous structure and improve productivity.

[0094] The non-solvent for the binder polymer is not particularly limited as long as it does not dissolve the first binder polymer and is partially compatible with the solvent for the first binder polymer. In an embodiment of the present invention, when the binder polymer further includes a second binder polymer in addition to the first binder polymer, the non-solvent may be one that does not dissolve both the first binder polymer and the second binder polymer.

[0095] In an embodiment of the present invention, the non-solvent for the binder polymer may include at least one selected from the group consisting of methanol, ethanol, isopropyl alcohol, butanol, ethyl acetate, and water.

[0096] In an embodiment of the present invention, when the binder polymer includes the second binder polymer in addition to the first binder polymer, the first binder polymer may exhibit faster phase separation behavior than the second binder polymer under phase separation conditions when forming a porous coating layer, and the second binder polymer may exhibit slower phase separation behavior than the first binder polymer under phase separation conditions when forming a porous coating layer, but is not limited thereto.

[0097] In the above case, the first binder polymer contained in the slurry migrates to the surface of the porous coating layer in contact with the non-solvent much faster than the second binder polymer, and may be located at the surface of the porous coating layer more abundantly than the second binder polymer (the first binder polymer content is higher than the weight ratio of the first binder polymer and the second binder polymer when initially added). In contrast, the second binder polymer may be permeated more slowly by the non-solvent than the first binder polymer, and may also have a relatively slow phase separation rate. Therefore, the second binder polymer may be present more abundantly (the second binder polymer content is higher than the weight ratio of the first binder polymer and the second binder polymer when initially added) inside the porous coating layer, i.e., between the porous polymer substrate and the inorganic particles.

[0098] In one embodiment of the present invention, by simultaneously including a first binder polymer and a second binder polymer as the binder polymer, the second binder polymer can contribute to improving the adhesive strength between the porous polymer substrate and the porous coating layer, and the first binder polymer can contribute to improving the adhesive strength between the surface portion of the porous coating layer and the electrode, thereby providing a separator with excellent adhesive strength to both the substrate and the electrode.

[0099] In one embodiment of the present invention, the drying can be carried out by a method known in the art, and can be carried out in a batch or continuous manner using an oven or a heated chamber at a temperature range that takes into account the vapor pressure of the solvent used. The drying is to remove most of the solvent present in the slurry, and it is preferable that this is done as quickly as possible in consideration of productivity, etc., and can be carried out for a time of, for example, 1 minute or less, preferably 30 seconds or less.

[0100] A lithium secondary battery can be manufactured by interposing the separator for a lithium secondary battery according to an embodiment of the present invention between a positive electrode and a negative electrode.

[0101] The lithium secondary battery including the separator for lithium secondary batteries according to one embodiment of the present invention includes a separator having excellent compression resistance, and thus can improve problems such as an increase in the rate of internal short circuits due to compression of the separator and a decrease in battery performance due to volume expansion of the negative electrode during charging and discharging.

[0102] The lithium secondary battery may include a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0103] The electrode to be used together with the separator for a lithium secondary battery according to an embodiment of the present invention is not particularly limited, and may be prepared in a form in which an electrode active material is bound to a current collector according to a conventional method known in the art.

[0104] Among the electrode active materials, non-limiting examples of the positive electrode active material include conventional positive electrode active materials that can be used in the positive electrode of conventional lithium secondary batteries. In particular, it is preferable to use lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide that is a combination of these.

[0105] Among the electrode active materials, non-limiting examples of the negative electrode active material include conventional negative electrode active materials that can be used in the negative electrode of conventional lithium secondary batteries, and in particular, lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, other carbons, and other lithium adsorbent materials are preferred.

[0106] Non-limiting examples of positive current collectors include foils made of aluminum, nickel, or combinations thereof, and non-limiting examples of negative current collectors include foils made of copper, gold, nickel, or copper alloys, or combinations thereof.

[0107] According to one embodiment of the present invention, the electrolyte used in the lithium secondary battery is + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.

[0108] The electrolyte injection may be performed at an appropriate stage during the battery manufacturing process depending on the manufacturing process and required properties of the final product, i.e., before the battery is assembled or at the final stage of the battery assembly.

[0109] According to a specific embodiment of the present invention, a process for applying the separator for a lithium secondary battery to a battery may include a lamination or stack process of the separator and an electrode and a folding process in addition to a general winding process.

[0110] According to a specific embodiment of the present invention, the separator for a lithium secondary battery may be interposed between a positive electrode and a negative electrode of a lithium secondary battery, and may be interposed between adjacent cells or electrodes when a plurality of cells or electrodes are assembled to form an electrode assembly. The electrode assembly may have various structures such as a simple stack type, a jelly roll type, a stack folding type, and a lamination-stack type. EXAMPLES

[0111] Hereinafter, the present invention will be described in detail with reference to examples and evaluation examples to help understand the present invention. However, the examples according to the present invention can be modified into various different forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.

[0112] Example 1-1 To acetone, 28 wt% of poly(vinylidene fluoride-co-hexafluoropropylene) (manufactured by Arkema) (VDF monomer content: HFP monomer content = 98:2) containing 2 wt% hexafluoropropylene monomer and 98 wt% vinylidene fluoride monomer as a first binder polymer, and 2 wt% of cyano resin (manufactured by Miwon Shoji) as a dispersant were added.

[0113] To this was added 70 wt % of TiO2 (Sigma-Aldrich, average particle size: 500 nm, Mohs hardness: 7.3), and the mixture was dispersed using a ball mill to prepare a slurry for forming a porous coating layer.

[0114] The slurry prepared as described above was coated on both sides of a polyethylene film (manufactured by SCK, thickness: 35 μm) by dip coating, and then humidified and phase-separated under conditions of 23° C. and 60% relative humidity to prepare a separator with a porous coating layer on both sides.

[0115] Example 1-2 A separator was produced in the same manner as in Example 1-1, except that 14 wt% of poly(vinylidene fluoride-co-hexafluoropropylene) (manufactured by Arkema) (VDF monomer content: HFP monomer content = 98:2) containing 2 wt% hexafluoropropylene monomer and 98 wt% vinylidene fluoride monomer was used as the first binder polymer, and 14 wt% of polyvinyl alcohol (manufactured by Sigma-Aldrich) was added as the second binder polymer.

[0116] Comparative Example 1-1 A separator was manufactured in the same manner as in Example 1-1, except that poly(vinylidene fluoride-hexafluoropropylene) (manufactured by Arkema) containing 20% ​​by weight of hexafluoropropylene monomer and 80% by weight of vinylidene fluoride monomer (VDF monomer content: HFP monomer content = 80:20) was used as the first binder polymer.

[0117] Comparative Example 1-2 A separator was produced in the same manner as in Example 1-1, except that poly(vinylidene fluoride-co-hexafluoropropylene) was not used and 28% by weight of polyvinyl alcohol (Sigma-Aldrich) was used.

[0118] Comparative Example 1-3 A separator was produced in the same manner as in Example 1-1, except that Al(OH)3 (manufactured by Huber, average particle size: 800 nm, Mohs hardness: 3.0) was used as the inorganic particles.

[0119] Comparative Example 1-4 A separator was produced in the same manner as in Example 1-2, except that Al(OH)3 (manufactured by Huber, average particle size: 800 nm, Mohs hardness: 3.0) was used as the inorganic particles.

[0120] Comparative Examples 1-5 A separator was produced in the same manner as in Comparative Example 1-1, except that Al(OH)3 (manufactured by Huber, average particle size: 800 nm, Mohs hardness: 3.0) was used as the inorganic particles.

[0121] Comparative Examples 1-6 A separator was produced in the same manner as in Comparative Example 1-2, except that Al(OH)3 (manufactured by Huber, average particle size: 800 nm, Mohs hardness: 3.0) was used as the inorganic particles.

[0122] Comparative Examples 1-7 A separator was produced in the same manner as in Example 1-1, except that Al2O3 (manufactured by Sumitomo, average particle size: 500 nm, Mohs hardness: 9.0) was used as the inorganic particles.

[0123] Comparative Example 1-8 A separator was produced in the same manner as in Example 1-2, except that Al2O3 (manufactured by Sumitomo Ltd., average particle size: 500 nm, Mohs hardness: 9.0) was used as the inorganic particles.

[0124] Comparative Example 1-9 A separator was produced in the same manner as in Comparative Example 1-1, except that Al2O3 (manufactured by Sumitomo Ltd., average particle size: 500 nm, Mohs hardness: 9.0) was used as the inorganic particles.

[0125] Comparative Example 1-10 A separator was produced in the same manner as in Comparative Example 1-2, except that Al2O3 (manufactured by Sumitomo Ltd., average particle size: 500 nm, Mohs hardness: 9.0) was used as the inorganic particles.

[0126] The compositions of inorganic particles, binder polymers, and dispersants contained in the porous coating layers in the separators manufactured in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 are shown in Table 1 below.

[0127] [Table 1]

[0128] Example 2-1 Cathode manufacturing An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector.

[0129] Li(Ni 0.3 Mn 0.4 Co 0.3 A slurry for forming a positive electrode active material layer was prepared by adding O2, PVDF as a binder, and Denka Black as a conductive material in a weight ratio of 93:4:3 to an N-methyl-2-pyrrolidone (NMP) solvent.

[0130] The slurry for forming a positive electrode active material layer was coated on both sides of the aluminum foil, and then dried and rolled to prepare a positive electrode.

[0131] Anode production A copper foil having a thickness of 10 μm was prepared as a negative electrode current collector.

[0132] A slurry for forming a negative electrode active material layer was prepared by adding SiO as a negative electrode active material, PVDF as a binder, and Denka Black as a conductive material to an N-methyl-2-pyrrolidone (NMP) solvent in a composition ratio of 97:2:1.

[0133] The negative electrode active material layer forming slurry was coated on both sides of the copper foil, and then dried and rolled to prepare a negative electrode.

[0134] The separator prepared in Example 1-1 was interposed between the positive electrode and the negative electrode, and a pressure of 6.5 MPa was applied at 70° C. to prepare a lithium secondary battery.

[0135] Example 2-2 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Example 1-2 was interposed between the positive electrode and the negative electrode.

[0136] Comparative Example 2-1 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-1 was interposed between the positive electrode and the negative electrode.

[0137] Comparative Example 2-2 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-2 was interposed between the positive electrode and the negative electrode.

[0138] Comparative Example 2-3 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-3 was interposed between the positive electrode and the negative electrode.

[0139] Comparative Example 2-4 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-4 was interposed between the positive electrode and the negative electrode.

[0140] Comparative Example 2-5 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-5 was interposed between the positive electrode and the negative electrode.

[0141] Comparative Example 2-6 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-6 was interposed between the positive electrode and the negative electrode.

[0142] Comparative Example 2-7 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-7 was interposed between the positive electrode and the negative electrode.

[0143] Comparative Example 2-8 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-8 was interposed between the positive electrode and the negative electrode.

[0144] Comparative Example 2-9 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-9 was interposed between the positive electrode and the negative electrode.

[0145] Comparative Example 2-10 A lithium secondary battery was produced in the same manner as in Example 2-1, except that the separator produced in Comparative Example 1-10 was interposed between the positive electrode and the negative electrode.

[0146] Evaluation example 1: Measurement of storage modulus of binder polymer at 70°C The storage modulus at 70° C. of the binder polymers used in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 (when two types were used, each of the two binder polymers) was set to 2 MPa and measured using a dynamic mechanical analysis (DMA) method.

[0147] The samples were prepared by dissolving the binder polymers used in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 in acetone, casting the resulting solution on a glass plate, and drying it at 80°C for 12 hours to obtain a film, which was then cut to a width of 5.3 mm, a length of 3 cm, and a thickness of 90 μm. The tensile force in the length direction of the sample was measured under conditions of an amplitude of 0.3 mm, a measurement temperature of 25°C to 90°C, a heating rate of 2°C / min, and a frequency of 1 Hz, to measure the storage modulus at 70°C.

[0148] The results are shown in Table 2 below.

[0149] [Table 2]

[0150] FIG. 1 shows the storage modulus with temperature change of the binder polymers used in Example 1-1, Comparative Example 1-1, and Comparative Example 1-2.

[0151] As can be seen from FIG. 1, it was confirmed that the storage modulus of the binder polymer used in Example 1-1 was significantly higher than the storage modulus of the binder polymers used in Comparative Examples 1-1 and 1-2.

[0152] In particular, from Table 2 and FIG. 1, it was confirmed that the storage modulus of the binder polymer used in Example 1-1 was 500 MPa or more, whereas the storage modulus of the binder polymer used in Comparative Example 1-1 and Comparative Example 1-2 was less than 500 MPa.

[0153] Evaluation Example 2: Measurement of separator air permeability, thickness reduction rate, and electrode adhesive strength The air permeability and electrode adhesive strength of the separators produced in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 were measured and are shown in Table 3 below.

[0154] In addition, the thickness reduction rates of the porous polymer substrates included in the separators produced in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 at 70° C. and 7.4 MPa were measured and are shown in Table 3 below.

[0155] Measurement of air permeability The air permeability (Gurley) of the separators produced in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 was measured using an EG01-55-1MR device manufactured by Asahi Seiko Co., Ltd. At this time, the air permeability value was measured by measuring the air permeability of 1 in of the separators produced in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 when 100 cc of air was blown under a pressure of 12.2 inH2O. 2 The time required for the air to pass through the cross section (seconds), i.e., the ventilation time, was expressed.

[0156] Measurement of thickness reduction rate of porous polymer substrates The separators prepared in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 were compressed at 70°C and 7.4 MPa using a hot press (QMESYS), and then washed with acetone to measure the thickness reduction rate of the porous polymer substrate contained in the separator. At this time, a PET film was placed between the separator and the hot press to apply pressure uniformly.

[0157] The thickness reduction rate of the porous polymer substrate at 70° C. and 7.4 MPa was calculated using the following formula. Thickness reduction rate of porous polymer substrate at 70°C and 7.4Mpa = (thickness of porous polymer substrate at initial manufacture - thickness of porous polymer substrate at 70°C and 7.4Mpa) / thickness of porous polymer substrate at initial manufacture

[0158] Measurement of electrode adhesion The separators produced in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-10 were stacked on the negative electrodes produced above, cut to a width of 25 mm, sandwiched between 100 μm PET films, and then bonded using a flat press. At this time, the conditions of the flat press machine were heating and pressing at 60° C. and a pressure of 6.5 MPa for 1 second. The bonded separator and negative electrode were attached to a slide glass using double-sided tape. A part of the separator adhesive surface (10 mm or less from the end of the adhesive surface) was peeled off and attached to a 25×100 mm PET film and a single-sided adhesive tape so that the length direction was connected.

[0159] Using a UTM device manufactured by Instron, a glass slide was clamped in the lower holder of the UTM device, and the separator and the attached PET film were clamped in the upper holder of the UTM device, and a force was applied at 300 mm / min and 180° to measure the force required to peel the separator and negative electrode.

[0160] [Table 3]

[0161] From Table 3, it can be seen that the separator prepared in Example 1-1 contains a first binder polymer having a storage modulus of 500 MPa or more at 70°C, and therefore the thickness reduction rate of the porous polymer substrate at 70°C and 7.4 MPa is significantly small, being 7% or less, and the separator also has excellent breathability.

[0162] The separator prepared in Example 1-2 contains a first binder polymer having a storage modulus of 500 MPa or more at 70°C, and a second binder polymer having a storage modulus of 50 MPa or less at 70°C but providing adhesive strength between the porous polymer substrate and the porous coating layer. As a result, the thickness reduction rate of the porous polymer substrate at 70°C and 7.4 MPa was significantly small at 7% or less, the air permeability was smaller than 2000 s / 100 cc, and it was confirmed that the separator had excellent electrode adhesion.

[0163] On the other hand, the separator prepared in Comparative Example 1-1 contained only a binder polymer having a storage modulus of less than 500 MPa at 70°C, and it was confirmed that the thickness reduction rate of the porous polymer substrate at 70°C and 7.4 MPa exceeded 7%.

[0164] The separator prepared in Comparative Example 1-2 contained only a binder polymer having a storage modulus of less than 500 MPa at 70°C. Therefore, the thickness reduction rate of the porous polymer substrate at 70°C and 7.4 MPa exceeded 7%, and it was confirmed that the pores of the porous coating layer were clogged due to the compression of the porous coating layer, resulting in a significant decrease in air permeability.

[0165] The separators manufactured in Comparative Examples 1-3 to 1-6 contained a first binder polymer having a storage modulus of 500 MPa or more at 70°C, but the inorganic particles having a Mohs hardness of less than 3.5 were unable to sufficiently absorb external stress, so the thickness reduction rate of the porous polymer substrate exceeded 7%. The porous coating layer was also compressed, and the pores of the porous coating layer were clogged, resulting in a significant reduction in air permeability.

[0166] The separators manufactured in Comparative Examples 1-7 to 1-10 contain a first binder polymer having a storage modulus of 500 MPa or more at 70°C. However, it was confirmed that inorganic particles having a Mohs hardness of more than 8.5 cause damage to the porous polymer substrate itself, resulting in a thickness reduction rate of the separator of 50% or more at 70°C and 7.4 MPa.

[0167] Evaluation example 3: Measurement of SEM image of separator cross section after lamination process Cross-sections of the separators of the lithium secondary batteries prepared in Example 2-2 and Comparative Example 2-2 were measured by SEM images, which are shown in FIG. 2 and FIG. 3, respectively.

[0168] From FIG. 2, it was confirmed that there was no significant difference in the thickness distribution of the separator throughout the entire separator in the lithium secondary battery produced in Example 2-2.

[0169] On the other hand, from FIG. 3, it can be seen that in the lithium secondary battery prepared in Comparative Example 2-2, a portion of the separator was locally and strongly compressed, resulting in a significant thickness reduction.

[0170] Evaluation example 4: Analysis of cycle life characteristics of lithium secondary batteries The lithium secondary batteries prepared in Example 2-1 and Comparative Example 2-1 were analyzed for cycle life characteristics based on the capacity when discharged at 25° C. and 0.44 C, and the results are shown in Table 4 below.

[0171] The resistance increase rate of the lithium secondary batteries prepared in Example 2-1 and Comparative Example 2-1 was measured at 25° C., SOC 50%, and 10 seconds, and is shown in Table 4 below.

[0172] [Table 4]

[0173] From Table 4, it can be seen that the cycle evaluation results show that the lithium secondary battery prepared in Example 2-1 has a superior capacity retention rate even after 700 cycles compared to the lithium secondary battery prepared in Comparative Example 2-1.

[0174] It was also confirmed that the lithium secondary battery produced in Example 2-1 had a significantly lower resistance increase rate than the lithium secondary battery produced in Comparative Example 2-1.

Claims

1. A porous polymer substrate; a porous coating layer disposed on at least one surface of the porous polymer substrate, the porous coating layer including inorganic particles having a Mohs hardness of 3.5 to 8.5 and a binder polymer; The binder polymer includes a first binder polymer having a storage modulus of 500 MPa or more at 70° C., The thickness reduction rate of the separator under the lamination conditions of the electrode and the separator is 7% or less; The separator for a lithium secondary battery is characterized in that the lamination conditions of the electrode and the separator are 70° C. and 7.4 MPa.

2. The inorganic particles are TiO 2 , SiO 2 2. The separator for a lithium secondary battery according to claim 1, comprising:

3. 3. The separator for a lithium secondary battery according to claim 1, wherein the first binder polymer comprises polyvinylidene fluoride-hexafluoropropylene containing 1 wt % to 3 wt % of hexafluoropropylene monomer, poly(acrylic acid)-poly(vinyl alcohol) copolymer, or two or more thereof.

4. The separator for a lithium secondary battery according to claim 1 , wherein the binder polymer further comprises a second binder polymer having a storage modulus of 50 MPa or less at 70° C.

5. 5. The separator for a lithium secondary battery according to claim 4, wherein a weight ratio of the first binder polymer to the second binder polymer is from 0.8:1 to 1.2:

1.

6. The second binder polymer is The separator for lithium secondary batteries according to claim 4 or 5, characterized in that it contains polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, or two or more of these.

7. The separator for a lithium secondary battery according to claim 1 , wherein the porous coating layer further comprises a dispersant.

8. 8. The separator for lithium secondary batteries according to claim 7, wherein the dispersant comprises a cyanoresin containing a CN (cyano group), carboxymethyl cellulose, polyacrylic acid, polymethacrylic acid, or two or more of these.

9. 9. The separator for a lithium secondary battery according to claim 1, wherein the inorganic particles are contained in an amount of 20% by weight to 99.9% by weight based on 100% by weight of the porous coating layer.

10. A battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, A lithium secondary battery, characterized in that the separator is the lithium secondary battery separator according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Separator for electrochemical element

    JP2010067653A

  • Separator for power storage device

    JP2011171290A

  • Separator for power storage device and method for manufacturing the same

    JP2017139117A

  • Doctor blade, coating device, and method of manufacturing laminated separator

    JP2017162803A

  • Laminated porous membrane, process for manufacturing same and separator for battery

    WO2014175050A1